EFEKTIFITAS STRATEGI PEMBELAJARAN GENERATIF TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA - Fazsry Anatriyana Fauzy (Jurnal Edukasi dan Penelitian Matematika, 2018)
Ability of mathematical understanding concepts is one of mathematics learning purpose. Observations which had been done in class X SMA Negeri 4 Solok showed that mathematics learning process was not able to improved students' mathematical understanding concepts optimally. This was cause by thelearning strategythat had not able to improved students' mathematical understanding concepts. One effort that could be done was to apply the Generative Learning Strategy. This type of research was descriptive and quasi-experimental with research design was Static Group Design. The results  showed that  the  development of  students‘s ability  of  mathematical  understanding  concepts after  the implementation of generative learning strategy had increased. Furthermore, based on the hypothesis test results could be concluded that ability of students’s mathematical understanding concepts who learned by used generative learning strategy was better than students‘s ability of mathematical understanding concepts who learned by used conventional learning in class XI IPA SMA Negeri 4 Solok. Keywords ― Ability of Mathematical Understanding Concepts, Mathematics Learning, Generative Learning Strategy.